Comparative study on anti-proliferative potentials of zinc oxide and aluminium oxide nanoparticles in colon cancer cells - Subramaniam, Vimala Devi; Ramachandran, Murugesan; Marotta, Francesco; Banerjee, Antara; Sun, Xiao Feng; Pathak, Surajit (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: Use of commercial products containing nanoparticles formulated from zinc oxide (ZnO) and aluminium oxide (Al2O-3) has increased significantly. These nanoparticles are widely used as ingredient in cosmetics, and also in food packaging industry although their toxicity status is yet to be studied. Here, we aimed to explore the effect of zinc oxide nanoparticles (ZnO-NPs) and aluminium oxide nanoparticles (ANPs) in human HT29 colon cancer cell line. Methods: In this study, ZnO-NPs were synthesized by chemical method and ANPs synthesized by sol-gel method and were characterized using UV-Vis spectroscopy, X ray diffraction and Transmittance electron microscopy. The effects of ZnO-NPs and ANPs was determined by cell viability, membrane integrity and colony formation potentials. Results: ZnO-NPs and ANPs inhibit HT29, colon cancer cell proliferation in a dose dependent manner, and affect the membrane potentials and also prevent the colony formation. Conclusions: The results suggest that ZnO NPs are found to be more effective than ANPs in reducing colon cancer cell proliferation.